2018
DOI: 10.1002/ehf2.12371
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dyspnoea onset in patients with acute heart failure: clinical and prognostic implications

Abstract: AimsDespite attempts to improve the management of patients with acute heart failure (HF), virtually all therapeutic agents investigated in large clinical trials failed to show any consistent reduction in mortality and morbidity. Complexity of the clinical syndrome of acute HF seems to be likely an underlying explanation. Traditionally, clinical trials studied mixed patient populations with acute HF, and only recently, better clinical characterization of patients has been proposed. Dyspnoea is the most common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
5
10
0
Order By: Relevance
“…Our study provides additional interesting finding that the patients with peripheral signs of congestion experienced longer duration of dyspnoea before admission to hospital than patients with pulmonary congestion, in whom dyspnoea onset was more rapid. The aforementioned conclusion also stays in agreement with our previous paper, in which we proved that patients with subacute onset of dyspnoea (>7 days preceding hospital admission) have poorer short‐term and long‐term outcomes in comparison with patients with acute onset (≤7 days) 17 . Almost every third studied patient with AHF manifested as peripheral congestion, either isolated or concurrent with pulmonary congestion, died during 12 months after the index hospitalization.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study provides additional interesting finding that the patients with peripheral signs of congestion experienced longer duration of dyspnoea before admission to hospital than patients with pulmonary congestion, in whom dyspnoea onset was more rapid. The aforementioned conclusion also stays in agreement with our previous paper, in which we proved that patients with subacute onset of dyspnoea (>7 days preceding hospital admission) have poorer short‐term and long‐term outcomes in comparison with patients with acute onset (≤7 days) 17 . Almost every third studied patient with AHF manifested as peripheral congestion, either isolated or concurrent with pulmonary congestion, died during 12 months after the index hospitalization.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate the complexity of dyspnoea pathophysiology and suggest that dyspnoea is not a simple equivalent of lung congestion assessed on physical examination 21,35,36 . These data are consistent with our previous study, in which we analysed the pattern of dyspnoea onset in AHF, and we have shown that only 26% of patients with dyspnoea at rest, as a major symptom of AHF on admission, presented moderate/severe pulmonary congestion 17 . Our study provides additional interesting finding that the patients with peripheral signs of congestion experienced longer duration of dyspnoea before admission to hospital than patients with pulmonary congestion, in whom dyspnoea onset was more rapid.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations